Sharia Banking Contract Model: Alternative Financing For the Agricultural Sector in Indonesia - Prayogi, Bagus; Ramadhan, Daffa Aulia (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: In the Islamic conceptualization, banking has a central position as a financing institution for every Muslim that is free from ribawi elements. Sharia banking has made various efforts, such as formulating innovative products to meet credit needs. Unfortunately, these efforts are hampered by several factors, especially the mode of Sharia banking and the limited knowledge of Sharia banking staff regarding fiqh. One of the Sharia banking products that cannot be implemented until now is contracts sallam. Though Salam contract can accommodate credit needs, especially for farmers, promptly. In this case, of course, Islamic banking needs to take a role and take action to meet the needs of these farmers. Objectives: So, this paper aims to elaborate and formulate a contract model salam in banking by considering the problems faced by sharia banks and farmers. The formulation of the problem is how the contract model salam in sharia banking for agricultural financing in Indonesia. Method The approach used in this paper is qualitative with the type of research being the analysis content Results: The result of this research is that a contract salam can be implemented in Sharia banking. However, it requires an integration model from Sharia banking to microfinance institutions so that contract financing salam can be accommodated very well. Implications: It is hoped that this research will have an impact in formulating contract models salam which so far cannot be implemented in sharia banking.